Regulation and limitations to fatty acid oxidation during exercise - Jeppesen, J.; Kiens, B. (The Journal of Physiology, 2012)
Fatty acids (FAs) as fuel for energy utilization during exercise originate from different sources: FAs transported in the circulation either bound to albumin or as triacylglycerol (TG) carried by very low density lipoproteins and FAs from lipolysis of muscle TG stores. Despite a high rate of energy expenditure during high intensity exercise the total FA oxidation is suppressed to below that observed during moderate intensity exercise. Although this has been known for many years, the mechanisms behind this phenomenon are still not fully elucidated. A failure of adipose tissue to deliver sufficient FAs to exercising muscle has been proposed, but evidence is emerging that factors within the muscle might be of more importance. The high rate of glycolysis during high intensity exercise might be the `driving force' via the increased production of acetyl-CoA, which in turn is trapped by carnitine. This will lead to decreased availability of free carnitine for long chain FA transport into mitochondria. This review summarizes our present view on how FA metabolism is regulated during exercise with a special focus on the limitations in FA oxidation in the transition from moderate to high intensity exercise in humans.